Exploring the Tourism Potentiality of Chuliban Hill in Dhankuta Municipality - Rai, Pradeep (CHINTAN-DHARA, 2022)
Chuliban Hill is a forest-covered hill situated in Dhankuta Municipality, ward numbers 7 and 8. The forest is owned and protected by three different forest user groups formed under the Division Forest Office of Dhankuta. For the past several years various attempts at developing the Chuliban Hill as a major tourist destination within Dhankuta Municipality have been made. But only a few attempts have been successful so far, and only a few domestic tourists do actually come to visit the place. Against this background, this research work explores the actual and optimum tourism potentiality of the Chuliban Hill and its developmental challenges by investigating the facts through close observation and interviewing all the major stakeholders. At the end of the research, it was found that the Chuliban Hill actually possesses a very high potentiality for developing as a major tourist destination within Dhankuta Municipality. The plans and projects towards this aim have also been made at different levels and times. However, insufficient budget allocation and lack of proper coordination between the Municipality and the local forest user groups, apart from the coronavirus, have been the major hindrances that have caused the failure in realizing the full potentiality of the Chuliban Hill.